Exploring Algal Metabolism: Insights from Metabolomics and Computational Approaches - Maria Carpena; Aurora Silva; Franklin Chamorro; Javier Echave; Ana Olivia S. Jorge; Maria Fátima Barroso; Miguel A. Prieto (Biology and Life Sciences Forum)
Algae, despite being labeled as an underexplored biological source of chemical constituents, remain inadequately studied in terms of their metabolism. Metabolomics has emerged as a high-throughput technology to investigate the full metabolic profile of samples that could aid in the understanding and characterization of algae. By delving into their primary composition, particularly polysaccharides and phycobiliproteins, alongside secondary metabolites like polyphenols and pigments, researchers can uncover not only their rheological and nutritional properties but also their diverse biological activities. Given the growing interest in algae in food and related industries, innovative approaches should be explored to enhance the value of their functional components. In this sense, in the context of contemporary in-silico studies, metabolomics should be paired with computational methodologies, to develop novel techniques for studying biomolecular interactions. Molecular docking has emerged, with the function of predicting the atomic-level interaction between small molecules (ligands) and target proteins (proteins). This synergistic approach integrating both technologies could allow us to characterize algal profiles, evaluate their potential for bioactive properties, and better understand their metabolism. This work explores the development of metabolomic and computational strategies targeted toward the functional characterization of algae. By harnessing these technologies, we can unlock new possibilities for using algae in various industrial applications, paving the way for sustainable and innovative solutions in the future.